2021
DOI: 10.1038/s41598-021-84058-3
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived mesenchymal stem cells differentiate into heterogeneous cancer-associated fibroblasts in a stroma-rich xenograft model

Abstract: Cancer-associated fibroblasts (CAFs) are the key components of the densely proliferated stroma in pancreatic ductal adenocarcinoma (PDAC) and contribute to tumor progression and drug resistance. CAFs comprise heterogeneous subpopulations playing unique and vital roles. However, the commonly used mouse models have not been able to fully reproduce the histological and functional characteristics of clinical human CAF. Here, we generated a human cell-derived stroma-rich CDX (Sr-CDX) model, to reproduce the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…It has become common knowledge in the field that CAFs have different cellular sources and that they can have different functions within a PDAC tumor depending on interactions with cancer cells and other factors. Indeed, there are indications that CAFs behave, or are influenced, differently depending on geographical factors and culture conditions such is the case in the work of Öhlund et al (2017) and a more recent study on AD-MSC differentiation into iCAFs vs. myCAFs (Miyazaki et al, 2021). Therefore, to be able to effectively and accurately model pancreatic cancer, we are in need of models that can (1) maintain the morphological and growth characteristics of parent tumors as well as their mutational profiles; (2) the models should also take non-cancer compartments into account by including most of the stromal cell types that are present in the in vivo setting; and (3) be able to recapitulate the phenotypes and functionality of different CAF populations and subsets in PDAC tumors.…”
Section: The Contribution Of Pre-clinical Models To Modeling Tumor-stroma Interactionsmentioning
confidence: 97%
See 1 more Smart Citation
“…It has become common knowledge in the field that CAFs have different cellular sources and that they can have different functions within a PDAC tumor depending on interactions with cancer cells and other factors. Indeed, there are indications that CAFs behave, or are influenced, differently depending on geographical factors and culture conditions such is the case in the work of Öhlund et al (2017) and a more recent study on AD-MSC differentiation into iCAFs vs. myCAFs (Miyazaki et al, 2021). Therefore, to be able to effectively and accurately model pancreatic cancer, we are in need of models that can (1) maintain the morphological and growth characteristics of parent tumors as well as their mutational profiles; (2) the models should also take non-cancer compartments into account by including most of the stromal cell types that are present in the in vivo setting; and (3) be able to recapitulate the phenotypes and functionality of different CAF populations and subsets in PDAC tumors.…”
Section: The Contribution Of Pre-clinical Models To Modeling Tumor-stroma Interactionsmentioning
confidence: 97%
“…However, it is not yet known how differently sourced MSCs contribute to CAF subsets in PDAC. A recent study showed that adipose tissue-derived MSCs could differentiate into two different CAF subpopulations: direct contact co-culture with a PDAC cell line could induce their differentiation toward either myCAF or iCAF phenotype, while an indirect co-culture induced differentiation into only iCAFs ( Miyazaki et al, 2021 ). This sheds light on the role of MSCs in feeding the CAF population, but whether this is the case for MSCs from other sources as well needs to be studied.…”
Section: The Cellular Origins Of Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Study shows that ADMSCs (adipose-derived mesenchymal stem cells) differentiate into pancreatic cancer-associated fibroblasts in vitro [ 55 ]. ADMSCs protect the lung from ischemia reperfusion (IR) injury by attenuating inflammation/oxidative stress/mitochondrial damage/autophagy signaling pathways [ 56 ].…”
Section: Effects Of Mitophagy On Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The mitochondrial fission and accompanying mitophagy by miR-351-5p/Miro2 axis is critical in hippocampal neural progenitor cell death, and a potential therapeutic target in AD [54] Moringin Moringin inhibits the expression of genes involved in mitophagy in human periodontal ligament stem cells [55] C89 (the small-molecule compound 89) C89 induced autophagy involves in development and death of female germ stem cells through PI3K-AKT pathway [56] Memantine Memantine enhances the mitochondrial degradation induced by iPSCs, and accelerated the clearance of damaged mitochondria through PINK1/parkin-mediated mitophagy [57] Pioglitazone Pioglitazone has a significant inhibitory effect on autophagy of bone marrow mesenchymal stem cells, and it can protect mesenchymal stem cells from p-methylphenol-induced mitochondrial dysfunction by upregulation of PINK1 [58] Printex 90 Printex 90 can inhibit the osteogenic differentiation and mitochondrial dysfunction of MSCs, and affect the regulation of mitochondrial biogenesis, kinetics and mitosis [59] Doxycycline (DOX)…”
Section: Gp78mentioning
confidence: 99%
“…This plasticity of MSCs and their self-renewal capacity make these cells promising therapeutic targets for various diseases, including cancer treatment and tissue regeneration. MSCs undeniably offer immense potential in the field of medicine; however, the cells also present potential danger due to their ability to differentiate into tumour-associated fibroblasts (34)(35)(36), which support tumour growth through their secretome (37,38) and resistance to apoptosis (39). Due to their conflicting role in cancer progression and regression, efforts to utilize MSCs in anticancer therapies have been unsuccessful.…”
Section: Introductionmentioning
confidence: 99%